Accidental poisoning with “Chinese chalk” - Martínez-Navarrete, J.; Loria-Castellanos, J.; Nava-Ocampo, A.A. (Acta Biomedica Atenei Parmensis, 2008)
We present a 1.5-year old, 11 kg, female infant with a history of bronchial hyper-responsiveness who accidentally ingested half of a “Chinese chalk”. A day later, the infant showed vomiting, cough, fever, drowsiness, and irritability and her clinical conditions progressively worsened. She was admitted to the emergency department with cough, respiratory distress, and hepatomegaly. It has been reported that the chalk may contain deltamethrin and cypermethrin. The patient was successfully treated with supportive therapy. This report identifies “Chinese chalk” as a potential source of accidental poisoning in children and should be considered as part of the differential diagnoses in the emergency rooms since poisoning with these compounds may be misdiagnosed as organophosphate poisoning due to the presentation of similar symptoms.